Public-Private Partnerships (PPP) in Technical Education: The Case of Egypt’s Applied Technology Schools (ATS) - Magdy, Youstina (AUC Knowledge Fountain, 2023)
Technical education is a form of education that gained momentum in the 1800s and was considered as a parallel distinct model to general education by the post-war period. Public-private partnerships (PPPs) were one of the scaling up and enhancement efforts of technical education. In Egypt, the technical secondary education system has various school models; however, it was until 2018, when we first see the implementation of an PPP model with the establishment of the Applied Technology Schools (ATS). ATS schools aim at supplying the labor market with experienced skillful competent graduates in the demanded sectors in the Egyptian labor market, and according to international standards. The system started with three pilot schools in the academic year 18/19 and currently it has over forty schools. Within this context, the PPP model adopted in the ATS system remained unstudied, and accordingly the challenges and opportunities to the model was unexplored. Through conducted interviews, the study explains how the ATS schools started in Egypt, its main stakeholders as well as the internal structure inside the ATS school. The study also maps how the PPP model is governed and coordinate in the ATS system. Given this mapping, the study then identifies the PPP model implemented as an operational and educational PPP, explaining the scope, scale, method, and motive of this PPP. Lastly, the study also pinpoints key challenges and opportunities for the currently implemented model of PPP, recommending potential ways of enhancement, which would be useful given the vision of expanding the model in the country to reach 420 by 2030.